Are My Neighbours Ageing Yet? Local Dimensions of Demographic Change in German Cities - Uwe Neumann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
In the discussion about demographic change, the regional dimension so far has played a subordinate role. Based on municipal data for the period between 1998 and 2008, this paper examines to what extent recent demographic change has affected the population of cities and neighbourhoods, focusing on the largest urban agglomeration in Germany, the Rhine-Ruhr conurbation in North Rhine-Westphalia. The local outcomes of demographic change are modified considerably by regional migration and interrelate closely with regional prosperity. The survey provides a precise outline of the interrelation between basic demographic characteristics and shifts in the composition of neighbourhood populations over the study period. The analysis shows that in the most thriving cities, there is a particularly strong tendency of young adults to separate from other demographic groups. In neighbourhoods where there is no such influx of younger people, particularly in low-density residential areas on the urban fringe, rapid demographic ageing aff ects neighbourhood populations and local economies. – – In der Debatte über die Auswirkungen des demographischen Wandels hat die regionale Dimension bislang eine vergleichsweise geringe Beachtung gefunden. Der vorliegende Beitrag liefert eine systematische Bestandsaufnahme des Zusammenhangs zwischen der lokalen Ausgangslage (Altersstruktur der Wohnbevölkerung, regionalökonomische Rahmenbedingungen) und der Bevölkerungsentwicklung in Städten und Stadtteilen während des Zeitraums von 1998 bis 2008. Die Analyse basiert auf kommunalen Daten, die für den größten deutschen Ballungsraum, die Rhein-Ruhr-Region, zusammengestellt wurden. Im Ergebnis wird festgestellt, dass in besonders prosperierenden Städten, in denen ein Zuzug von Personen im Erwerbsalter stattfindet, eine starke räumliche Ballung dieser Altersgruppen in ausgewählten Stadtteilen zu beobachten ist. In anderen Nachbarschaften, vor allem in Einfamilienhausgebieten des Stadtrands bzw. Stadt-Umlands, findet ein rascher Alterungsprozess der Wohnbevölkerung statt, der mit erheblichen lokal-ökonomischen Implikationen verbunden ist.
Keywords: J11; R23; 330; Demographic change; neighbourhoods; segregation; migration